ANALISIS PERSIAPAN DAN PEMANFAATAN SIMRS DI RS BALIMBINGAN KABUPATEN SIMALUNGUN - Batu Bara, Muhammad Hanafi; Lewis, Andreas (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2024)
The generation and processing of SIMRS is a responsibility of every hospital. Improvements in operational reporting, decision-making speed, problem-identification accuracy and speed, strategy formulation ease in managerial implementation, work culture, transparency, unit coordination, system understanding, and cost reduction administration are all necessary for the successful processing and development of SIMRS to enhance and support hospital health service processes. There has been no integration between the Balimbingan Hospital's SIMRS processing and the financial and administration department from 2018 to 2021. In light of these issues, it is critical to examine the challenges encountered by Balimbingan Hospital in 2021 while implementing the Hospital Management Information System in Simalungun Regency, North Sumatra Province. This study employs a descriptive model with a System of Action unit of analysis and is qualitative in nature. It takes the form of a case study. Presented findings from an investigation of the implementation and utilization of SIMRS at Balimbingan Hospital in Simalungun Regency through the use of participant observation and in-depth interviews. People who are familiar with the issues under investigation and can provide insight into the current state of affairs are called